Formation Of Methodological Components For Solving NonStandard Problems In Mathematics - Ubaydulloyev Farrukh Barakayevich (Genius Journals, 2024)
Below in this article, an opinion is expressed about the necessary, targeted introduction of methodological innovations aimed at solving non-standard problems on the topic of mathematics “Pythagorean Theorem” among students of general secondary education, special and presidential schools.
Keywords: innovation; State educational standard; qualification requirements